In Search of Workers' Real Effort Reciprocity - A Field and a Laboratory Experiment - Heike Hennig-Schmidt; Bettina Rockenbach; Abdolkarim Sadrieh (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
We present a field experiment to assess the effect of own and peer wage variations on actual work effort of employees with hourly wages. Work effort neither reacts to an increase of the own wage, nor to a positive or negative peer comparison. This result seems at odds with numerous laboratory experiments that show a clear own wage sensitivity on effort. In an additional real-effort laboratory experiment we show that explicit cost and surplus information that enables to exactly calculate employer's surplus from the work contract is a crucial pre-requisite for a positive wage-effort relation. This demonstrates that employee's reciprocity requires a clear assessment of the surplus at stake.
urn:nbn:de:bvb:19-epub-13495-3
Keywords: C91; C92; J41; 330; efficiency wage; reciprocity; fairness; field experiment; real effort